A Pathogenic Relationship Between a Regulator of the Actin Cytoskeleton and Serum Response Factor - Verdoni, Angela M. (Genetics Society of America, 2010)
Cell hyperproliferation, inflammation, and angiogenesis are biological processes central to the pathogenesis of corneal disease, as well as other conditions including tumorigenesis and chronic inflammatory disorders. Due to the number of disease conditions that arise as a result of these abnormalities, identifying the molecular mechanisms underlying these processes is critical. The avascular and transparent cornea serves as a good in vivo model to study the pathogenesis of cell hyperproliferation, inflammation, and angiogenesis. Corneal disease 1 (Dstn(corn1)) mice are homozygous for a spontaneous null allele of the destrin (Dstn) gene, which is also known as actin depolymerizing factor (ADF). These mice exhibit abnormalities in the cornea including epithelial cell hyperproliferation, stromal inflammation, and neovascularization. We previously identified that the transcription factor, serum response factor (SRF) and a number of its target genes are upregulated in the cornea of these mice. In this study, we show that conditional ablation of Srf in the corneal epithelium of a diseased Dstn(corn1) cornea results in the rescue of the epithelial cell hyperproliferation, inflammation, and neovascularization phenotypes, delineating an epithelial cell-specific role for SRF in the development of all of these abnormalities. Our study also demonstrates that Dstn is genetically upstream of Srf and defines a new functional role for SRF as the master regulator of a hyperproliferative, inflammatory phenotype accompanied by neovascularization.